Proposal of criteria for Systemic Budgetary Planning: Pix Amendments, Secret Budget and the Urgency of the Allocative Effectiveness Matrix (REMUNOM, 2026)
This article analyzes the recent transformation of Brazilian budgetary governance resulting from the expansion of parliamentary amendments, with a strong emphasis on the secret budget and special transfers, and their effects on the dynamics of allocating discretionary spending by the Union between 2020 and 2025. It starts from the hypothesis that the expansion of transfer modalities linked to parliamentary initiative, associated with the simplification of administrative procedures and the reduction of prior technical requirements, has produced a growing dissociation between budget execution and traditional state planning instruments. The research combines a literature review in the fields of Financial, Administrative and Constitutional Law and fiscal federalism with institutional analysis of budgetary norms, judicial decisions and empirical evidence from reports by control bodies and case studies of municipal execution. The investigation examines whether the accelerated decentralization of resources, when decoupled from structured planning criteria and administrative capacity, tends to generate allocative inefficiencies and institutional liabilities in subnational entities. The reflection indicates that the expansion of parliamentary transfers in modalities with less traceability and less programmatic linkage has increased the fragmentation of federal budget execution, reducing the capacity for coordination of national public policies and increasing the risk of investments with low administrative sustainability in the beneficiary municipalities. At the same time, the study identifies that amendments linked to structured public policies and national management systems with transparency criteria are more likely to generate effective results. As an analytical contribution, the article proposes the Allocative Effectiveness Matrix (AEM), a conceptual model that integrates four dimensions of fiscal governance - transparency of transfers, social vulnerability of the beneficiary territory, alignment with state planning and administrative capacity of the executing entity - allowing the evaluation of the institutional consistency of budget allocation decisions. The matrix is ​​presented as an analytical instrument capable of supporting empirical evaluations of public spending and guiding the improvement of the governance of intergovernmental transfers in the context of federalism.